Desktop-Based Employee Data Management Information System at the Public Works Office of Pidie Jaya Regency - Safrizal (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Public Works Office (PU) of Pidie Jaya Regency is a government institution engaged in infrastructure and facility development. In the process of employee data management, the Public Works Office (PU) of Pidie Jaya Regency uses office applications such as Microsoft Office. The activities in the office, ranging from document reception to report generation, have been inefficient due to the semi-computerized nature of the report recording. The purpose of this thesis is to design an employee data management application, create a computerized data storage system, reduce data duplication and report errors, and analyze the system used at the Public Works Office (PU) of Pidie Jaya Regency. Based on research and observations conducted at the Public Works Office (PU) of Pidie Jaya Regency, it can be concluded that the implementation of this employee information system at the Public Works Office (PU) of Pidie Jaya Regency is effective and accurate, particularly in the human resources department. It makes obtaining employee information easier. This information system can address issues often encountered at the Public Works Office (PU) of Pidie Jaya Regency, such as difficulty in monitoring and overseeing employee data and reports. It helps prevent delays in generating annual and periodic employee reports, and facilitates the development of an information system program to obtain high-quality information